Legal Authority and Judicial Legitimacy: The Role of the Compilation of Islamic Law in Shaping Binding Religious Court Decisions - Moh. Rivai; Asmuni; Hariyanto (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2026)
This study examines the role of the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) as a normative foundation in shaping the legal authority and judicial legitimacy of Religious Court decisions in Indonesia. Although the KHI was formally established through a Presidential Instruction rather than a statutory regulation, it has become one of the primary legal references in adjudicating Islamic family law disputes within Religious Courts. This condition raises important questions regarding the extent to which the KHI possesses binding legal force and contributes to the legitimacy of judicial decisions. Using a normative juridical approach, this research analyzes statutory regulations, judicial doctrines, and court practices related to the implementation of the KHI in Religious Courts. The study finds that the KHI functions not merely as a complementary guideline but as a substantive legal instrument that strengthens consistency, legal certainty, and judicial reasoning in Islamic family law adjudication. Furthermore, the KHI plays a significant role in bridging classical Islamic jurisprudence with the modern Indonesian legal system, thereby reinforcing the authority of Religious Courts in resolving disputes. The study concludes that the KHI has developed into a quasi-codified Islamic legal framework that substantially influences the binding character and legitimacy of Religious Court decisions in Indonesia.